A review of β-glucans as a growth promoter and antibiotic alternative against enteric pathogens in poultry. Issue 3 (1st September 2017) - Anwar, M.I.; Muhammad, F.; Awais, M.M.; Akhtar, M.
Abstract : The emergence of microbial challenges in commercial poultry farming causes significant economic losses. Vaccination is effective in preventing diseases of single aetiology while antibiotics have an advantage over vaccination in controlling diseases of multiple aetiologies. As the occurrence of antibiotic resistance is a serious problem, there is increased pressure on producers to reduce antibiotic use in poultry production. Therefore, it is essential to use alternative substances to cope with microbial challenges in commercial poultry farming. This review will focus on the role of β-glucans originating from yeast cell wall (YCW) as a growth promoter and antibiotic alternative. β-glucans have the ability to modulate the intestinal morphology by increasing the number of goblet cells, mucin expression and cells expressing secretory IgA (sIgA) with increased sIgA in the intestinal lumen and decreased bacterial translocation to different organs. β-glucans also increase the gene expression of tight junction (TJ) proteins which maintain the integrity of the intestinal wall in broiler chickens. However, further studies are required to optimise the dosage and source of β-glucans to determine effects on growth performance and mechanisms against enteric pathogens.